Antibody anti-dengue profile in dengue hemorrhagic fever patients at dr. Soetomo hospital, surabaya - Waskito, Langgeng A; Notopuro, Paulus B; Endraswari, Pepy Dwi (Folia Medica Indonesiana, 2016)
Dengue hemorrhagic fever is one infectious diseases that have high case fatality rate in Indonesia. The aim of this study was to descibe the antibody anti-dengue profile in dengue hemorrhagic fever patients at Dr. Soetomo Hospital Surabaya. This study was epidemiological descriptive study to aims prevalence primary and secondary infection of dengue hemorrhagic fever and its clinical appearances. This study used 85 samples by taking medical record data of IgM and IgG anti-dengue serologic test from Internal Medicine Department, Dr. Soetomo Hospital, Surabaya, between January to December 2010. The data were collected and analyzed in diagrams and tables. Result of this study showed 25 (29,4%) patients had positive IgM serologic test, 14 (16,4%) patients had positive IgG serologic test and 46 (54,2%) patients had positive IgM and IgG serologic test. In primary infections, the history of fever was 3.8±1.2 days; platelet counts 58,6±21,4/ml and bleeding sign 37% of 25 patients. In secondary infections, the history of fever was 4.28±1.15 days; platelet count was 44,17±24,2/ml and bleeding sign 52% of 60 patients. In conclusion, patients with secondary infection have higher prevalence than primary infection. Then in secondary infection had more severe clinical appearance than primary infection.